Modernization of the pedagogical system of tertiary education in higher education institutions - Ponomarova, Halyna; Kharkivska, Alla; Petrychenko, Larysa (My University, 2021)
In the framework of the research, the team of authors analyzed the main issues of education development in Ukraine and proved that the pedagogical process of future teachers’ tertiary education in higher education institutions needs constant modernization. In accordance with modern requirements (world trends, democratic values, principles of market economy, modern scientific and technical achievements; updating of methodological tools, expansion of innovative approaches to teacher training, etc.), new systems appear. They involve conceptual ideas, innovative theories and approaches to the strategy and main directions of improving national education. Therefore, the purpose of the collective monograph is to analytically consider the theory and practice of education, to determine the nature and dynamics of institutional changes in the educational paradigm in general and its specific areas or components in particular. Awareness of the conclusions made in the collective monograph will contribute to updating the pedagogical system of tertiary education in higher education institutions, future teachers’ comprehensive development; promote effective improvement of the quality of their training, increase the number of competitive professionals and increase the competitiveness of domestic higher education institutions in the international labour market
Modernization of the pedagogical system of tertiary education in higher education institutions : collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Kharkiv : Publishing house Education and Science s.r.o., 2021. – 464 с.
Keywords: вища освіта, модернізація, педагогічна система; higher education, modernization, pedagogical system